Effects of fertilization methods and film removal periods on soil nutrients and microbial community structure in tobacco fields of Southern Anhui Province - Shen, Chen; Yan, Yifeng; Pei, Zhouyang; Riaz, Muhammad; Dong, Hongxu; Liu, Zhiyuan; Yin, Long; Jiang, Chaoqiang; Xia, Hao (Frontiers in Environmental Science, 2025)
The rational application of fertilization methods and the timing of film removal are crucial for enhancing tobacco yield and quality, as well as for promoting soil health. In our study, we established fertilization methods (hole fertilization and band fertilization) and film removal timing treatments (film removal 30 days after transplanting, T1; 60 days after transplanting, T2; and no film removal, T3). We analyzed differences in soil nutrients, microbial community composition, and tobacco growth under different treatments. The results showed that, compared with other treatments, the combination of hole fertilization and T2 significantly promoted tobacco growth. Compared to band fertilization, hole fertilization increased plant height, as well as the area of middle and upper leaves, by 0.62%–5.01%, 4.71%–9.85%, and 4.71%–9.67%, respectively. In addition, root length, average diameter, root volume, number of tips, forks, and crossings all showed varying degrees of improvement with hole fertilization. Furthermore, hole fertilization combined with the T2 treatment contributed to enhanced soil pH, nutrient availability, and bacterial diversity. At the maturity stage, soil pH and soil organic matter (SOM) increased by 0.26–0.35 units and 9.09%–16.44%, respectively, with hole fertilization compared to band fertilization. Moreover, these agronomic practices influenced the relative abundance of functional microorganisms (p_Nitrospirota, p_Desulfobacterota, and p_Actinobacteriota) by regulating soil nutrient levels. In conclusion, the use of hole fertilization combined with film removal 60 days after transplanting effectively improves soil chemical properties, optimizes the microbial community structure, and increases tobacco yield in southern Anhui, representing an efficient fertilization management strategy.